Impact of Consistency in Daily Device Use on Speech Perception Abilities in Children with Cochlear Implants: Datalogging Evidence. - Easwar, Vijayalakshmi; Sanfilippo, Joseph; Papsin, Blake; Gordon, Karen (Journal of the American Academy of Audiology, 2018)
Background: Cochlear implants (CIs) give children with severe to profound hearing loss access to sound. There appears to be a dose effect of sound exposure on speech perception abilities as shown by the positive influence of early implantation and CI experience. The consistency in device use per day could also affect sound dose, potentially affecting perceptual abilities in children with CIs. Purpose: The objectives of the present study were to identify the impact of consistency in device use on: (1) speech perception abilities and (2) asymmetry in speech perception abilities between bilateral CIs. Research Design: Retrospective analysis. Study Sample: To achieve the first objective, data from 65 children (age range at speech test: 1.91-18.05 yrs) with one (unilaterally implanted or bimodal) or two CIs (sequentially or simultaneously implanted) were included. A subset of data from 40 children with bilateral CIs was included to achieve the second objective. Of the 40 children with two CIs, 15 received their CIs sequentially. Data Collection and Analysis: Device use information was extracted from datalogs stored in personal speech processors using custom software. Speech perception scores per CI collected in quiet were also evaluated. Multiple regression was used to assess the impact of daily CI use, while controlling for factors previously identified to affect speech perception: age at speech test, length of pre-CI (acoustic) hearing experience, length of CI hearing experience, and order of CI for the first objective, and CI category (simultaneous/sequential implantation), interimplant delay, and length of CI experience for the second objective. Results: On average, children wore their CIs for 11.59 ± 2.86 hours/day and, with one CI, exhibited 65.07 ± 22.64% accuracy on speech perception tests. Higher monaural speech perception scores were associated with longer everyday CI use and CI experience (p < 0.05). Among children with bilateral CIs, those with simultaneously implanted CIs and similar bilateral hearing experience demonstrated a small but significant right ear advantage with higher speech perception scores when using the right rather than left CI (mean difference = 4.55 ± 9.83%). The asymmetry in speech perception between CIs was larger and more variable in children who received their CIs sequentially (mean difference CI1-CI2 = 27.48 ± 24.87%). These asymmetries decreased with longer/consistent everyday use of the newer CI (p < 0.05). Yet, despite consistent everyday device use of the second CI (>12 hours/day), only a small proportion of children implanted sequentially (one out of seven children) achieved symmetrical function similar to children with simultaneously received bilateral CIs. Conclusions: Consistent everyday CI use contributes to higher speech perception scores. Although consistent CI use can help reduce the asymmetry in speech perception abilities of children with sequentially implanted CIs subsequent to interimplant delay, residual asymmetry often persists.